Self-Protected Mobile Agent Paradigm for DDoS Threats Using Block Chain Technology - Nasr, Mona (International journal of advanced networking and applications, 2019)
This paper describes Mobile Agents paradigm for tracking and tracing the effects of Denial of Service security threat in Mobile Agent System, an implementation of this paradigm has been entirely developed in java programming language. The proposed paradigm considers a range of techniques that provide high degree of security during the mobile agent system life cycle in its environment. This paper highlights the spot to two main design objectives: The importance of including various supportive types of agents within a system e.g., police agents, service agents, ...etc. Second: Evaluation analysis and number of checks to be done to trace the Mobile Agents if denial of the provided services during its path. Evaluation analysis for detecting tolerance differences for the calculated agent's route before and during its journey, storing agent transactions, storing snapshots of agent state information, checking from time to time agent status and task completeness and lastly guard agent checks the changed variables of migrated agent. During tracing and monitoring Mobile Agents, the initiator node may destroy it and continue with another. In this paper a new paradigm is presented that detects and eliminate with high probability, any degree of tampering within a reasonable amount of time, also provide the ability of scalability of security administration.